Askin Tumor: A Case Report of a Rare Tumor - Ningthoujam Dinita Devi; Deiwakor Chyrmang; Kishalay Baidya; Yumkhaibam Sobita Devi (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2021)
Askin tumor is a rare malignant neoplasm of neuro-ectodermal origin that emerges from the soft tissue of the thoraco-pulmonary wall and has aggressive activity. This paper presents a study on a 10-year-old boy having breathing difficulty and mass on the anterior portion of the left thoracic wall. On examination, there was a mass on the left anterior chest wall measuring 13x13 cm2, which was hard, tender, and fixed to the chest wall. There was associated pleural effusion and infiltration into the left lung. Histopathology confirmed primitive neuro-ectodermal tumor (Askin tumor) with IHC marker CD99 positive. Chemotherapy was used to treat the patient. Early detection of this tumor would necessitate a high index of suspicion, allowing for a better prognosis and result. The overall prognosis is poor due to the higher rate of local recurrence.